TATALAKSANA HIPERTENSI PULMONAL PADA ANAK - Herlina Dimiati; Poppy Indriasari (Jurnal Kedokteran Syiah Kuala, 2012)
Definisi HP: yaitu tekanan arteri pulmonal rata – rata lebih dari 25 mmHg dalam keadaan istirahat, atau ≥ 30 mmHg selama aktivitas. Gejala yang timbul tidak spesifik dan sering sulit dibedakan dengan penyakit paru ataupun penyakit kardiovaskular. Dalam 5 tahun terakhir terjadi perubahan yang dramatis dalam pengobatan HP dan memberikan kemajuan signifikan.Abstract : Pulmonary hypertension (PH) is relatively common in children than in adults. PH is defined as mean pulmonary artery pressure of more than 25 mmHg at rest or more than 30 mmHg during exercise. The symptoms of PH are nonspecific and are often difficult to differentiate from those of other pulmonary or cardiovascular diseases. The management of the condition has changed dramatically in the past 5 years and resulted in significant improvements.